The role of CEO transformational leadership and innovation climate in exploration and exploitation. Issue 1 (13th June 2018) - Zuraik, Abdelrahman; Kelly, Louise
Abstract : Purpose: The purpose of this paper is to investigate the relationship among CEO transformational leadership, innovation climate and organizational innovation through exploration and exploitation. Design/methodology/approach: A questionnaire, designed as a self-reported survey, was distributed to individuals working in teams in US-based corporations, with a collected sample size of 215 organizations. Findings: Results show that CEO transformational leadership has a direct positive effect on organizational innovation and an indirect effect through innovation climate. CEO leadership is more impactful for exploitation, compared to innovation climate, which has more influence on exploration. Research limitations/implications: This study is the first to integrate CEO transformational leadership and innovation climate with exploration and exploitation outcomes. A research limitation is that there is a higher percentage of female than male respondents and a lower of percentage of female CEOs in this study. A further limitation is self-report which can lead to common method bias. Practical implications: The close connection among CEO transformational leadership, innovation climate and organizational innovation suggests that evaluating, supporting and training CEO transformational leadership becomes a vital activity for boards, investors and managers. If management wants to increase exploration, they should pay particular attention to creating a climate that is supportive of innovation. Organizations should recruit and train CEOs for transformational leadership and regularly assess climate to ensure innovation results. Originality/value: The main contribution of this study is highlighting the role of innovation climate as a mediator between CEO transformational leadership and the outcome of organizational innovation which is measured by exploration and exploitation activities.